Canine Cutaneous Leishmaniasis: Dissemination and Tissue Tropism of Genetically Distinct Leishmania (Viannia) braziliensis Populations - Guilherme Marx de Oliveira; Maria de Fátima Madeira; Fernanda Santos Oliveira; Marize Quinhones Pires; Raquel da Silva Pacheco (Veterinary Medicine International)
Little is known regarding the internal dissemination of initial cutaneous lesions and tissue tropism of Leishmania (Viannia) braziliensis populations in naturally infected dogs. The aim of this study was to investigate genetic polymorphisms of L. (V.) braziliensis populations in different anatomic sites of naturally infected dogs by using polymerase chain reaction (PCR) and low-stringency single specific primer-PCR (LSSP-PCR) techniques. The amplified products were analyzed by LSSP-PCR to investigate the genetic variability of the parasite populations present in different anatomical sites. Twenty-three out of the 52 samples gave PCR-positive results. The existence of L. (V.) braziliensis strains that remained restricted to cutaneous lesions and others showing characteristics of dissemination to internal organs and healthy skin was observed. LSSP-PCR and numerical analyses revealed that parasite populations that do not disseminate were genetically similar and belonged to a separate phenetic cluster. In contrast, populations that showed spreading to internal organs displayed a more polymorphic genetic profile. Despite the heterogeneity, L. (V.) braziliensis populations with identical genetic profiles were observed in popliteal and cervical lymph nodes of the same animal. Our results indicate that infection in dogs can be manifested by dissemination and tissue tropism of genetically distinct populations of L. (V.) braziliensis.